2020
DOI: 10.1016/j.xkme.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Kidney Failure Risk Equation for Prediction of Allograft Loss in Kidney Transplant Recipients

Abstract: Rationale & Objective The Kidney Failure Risk Equation (KFRE) is a simple widely validated prediction model using age, sex, estimated glomerular filtration rate, and urinary albumin-creatinine ratio to predict the risk for end-stage kidney disease. Data are limited for its applicability to kidney transplant recipients. Study Design Validation study of the KFRE as a post hoc analysis of the Folic Acid for Vascular Outcomes Reduction in Transplantation (FAVORIT) Trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…A recent study found that among patients with an eGFR <15 ml/min per 1.73 m 2 , the eGFR and KFR equation had a similar predictive value for estimating time to kidney failure. 26…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that among patients with an eGFR <15 ml/min per 1.73 m 2 , the eGFR and KFR equation had a similar predictive value for estimating time to kidney failure. 26…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for low rates of preemptive listings among these candidates and others with high priority for kidney transplants are not totally clear and warrant further study, although demographic and socioeconomic factors are likely contirbutors 21,22 . Additional strategies to improve early wait‐listing might include refitting pediatric kidney failure risk equations to improve their performance in organ transplant recipients, as has been performed in adults, to help providers identify which prior transplant recipients have a risk of needing a transplant in the near future 23–27 . Alternatively, it is possible that some centers may intentionally delay consideration for a retransplant for select candidates with prior nonadherence until concerns for future adherence are addressed, but we are unable to test this hypothesis with available data.…”
Section: Discussionmentioning
confidence: 99%
“…Calibration of the model was also good. Finally, Chu et al examined a cohort of 2889 posttransplant patients more than 6 months posttransplant, provided their eGFR was less than 60 ml/min/1.73 m 2 [22 ▪ ]. Here, the four-variable KFRE performed well at 2 and 5 years, with C-statistics of 0.85 (95% CI: 0.81–0.88) and 0.81 (95% CI: 0.78–0.84).…”
Section: Kidney Failure Risk Prediction: Performance In Novel Populat...mentioning
confidence: 93%